Spectral Flattening at Low Frequencies in Crab Giant Pulses - Meyers, B.; Tremblay, S.; Bhat, N.; Shannon, R.; Kirsten, F.; Sokolowski, M.; Tingay, Steven; Oronsaye, S.; Ord, S. (-, 2017)
We report on simultaneous wideband observations of Crab giant pulses with the Parkes radio telescope and the Murchison Widefield Array (MWA). The observations were conducted simultaneously at 732 and 3100 MHz with Parkes, and at 120.96, 165.76 and 210.56 MHz with the MWA. Flux density calibration of the MWA data was accomplished using a novel technique based on tied-array beam simulations. We detected between 90-648 giant pulses in the 120.96-210.56 MHz MWA subbands above a $ 5.5σ $ threshold while in the Parkes subbands we detected 6344 and 231 giant pulses above a threshold of $ 6σ $ at 732 and 3100 MHz, respectively. We show, for the first time over a wide frequency range, that the average spectrum of Crab giant pulses exhibits a significant flattening at low frequencies. The spectral index, $ α $, for giant pulses evolves from a steep, narrow distribution with a mean $ α=-2.6 $ and width $σ_α=0.5 $ between 732 and 3100 MHz, to a wide, flat distribution of spectral indices with a mean $ α=-0.7 $ and width $ σ_α=1.4 $ between 120.96 and 165.76 MHz. We also comment on the plausibility of giant pulse models for Fast Radio Bursts based on this spectral information.